Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2116/analsci.22.1189
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Daunomycin in Human Plasma and Urine by Using an Interference-free Analysis of Excitation-Emission Matrix Fluorescence Data with Second-Order Calibration

Abstract: IntroductionDaunorubicin (DNR), discovered in the early 1960s, is an anthracycline antibiotic with antiblastic and anticancer activity, which is linked by the formation of intercalative complexes with DNA and the inhibition of both DNA and RNA synthesis. Although it still remains an important component for many current chemotherapy protocols of acute and myelogenous leukemia, cardiotoxicity is a serious problem, especially in the case of overdoses.1 It is thus important for determining DNR in human plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Com- parison with COOH/ITO electrode, 20 the method had lower detection limit. Table II and Table III could explain the performance of the NH 2 /ITO electrode with other modified electrodes and conventional techniques reported in literatures, [15][16][17][18][19][20][21][22][23][24] respectively." The two tables showed that the proposed method had lower detection limit and wider linear range.…”
Section: Electrochemical Determination Of Daunorubicin In Human Urine-mentioning
confidence: 99%
See 1 more Smart Citation
“…Com- parison with COOH/ITO electrode, 20 the method had lower detection limit. Table II and Table III could explain the performance of the NH 2 /ITO electrode with other modified electrodes and conventional techniques reported in literatures, [15][16][17][18][19][20][21][22][23][24] respectively." The two tables showed that the proposed method had lower detection limit and wider linear range.…”
Section: Electrochemical Determination Of Daunorubicin In Human Urine-mentioning
confidence: 99%
“…Daunorubicin is ofz E-mail: hujingbo@bnu.edu.cn ten used as an anticancer drug with its clinical efficacy against a wide range of malignancies and anti-tumor properties. 14 There are some instrumental methods for daunorubicin detection, such as capillary electrophoresis, 15 high performance liquid chromatography, 16 fluorescence spectrometry, 17 and resonance Rayleigh scattering. 18 In these methods, considerable sample handling was required.…”
mentioning
confidence: 99%
“…Therefore, there is a great need for the researchers to develop in silico methods to deconvolute the gene expression profiles of a heterogeneous clinical sample into the cell type‐specific gene expression profiles and estimate the corresponding cell contents . The multivariate curve resolution algorithms have achieved great success in quantitative analysis in chemistry and in related areas such as environmental science, food science, and pharmaceutical analysis . Several computational approaches based on the multivariate curve resolution algorithms have been proposed to deconvolute the gene expression profiles of specific cell types from the mixed signals generated by DNA microarrays.…”
Section: Introductionmentioning
confidence: 99%
“…A unicidade do PARAFAC tem sido amplamente explorada em química analítica [93, [137][138][139] e chamada vantagem de segunda ordem. Isto ocorre, pois, em uma decomposição única é possível obter os perfis puros dos sinais em ambos os modos.…”
Section: Parafacunclassified